Recovery and Analysis of Bacterial Membrane Vesicle Nanoparticles from Human Plasma Using Dielectrophoresis - Jason P. Ware; Delaney K. Shea; Shelby L. Nicholas; Ella A. Stimson; Jessica L. Riesterer; Stuart D. Ibsen (Biosensors, 2024)
Bacterial membrane vesicle (BMV) nanoparticles are secreted naturally by bacteria throughout their lifecycle and are a rich source of biomarkers from the parent bacteria, but they are currently underutilized for clinical diagnostic applications, such as pathogen identification, due to the time-consuming and low-yield nature of traditional recovery methods required for analysis. The recovery of BMVs is particularly difficult from complex biological fluids. Here, we demonstrate a recovery method that uses dielectrophoretic (DEP) forces generated on electrokinetic microfluidic chips to isolate and analyze BMVs from human plasma. DEP takes advantage of the natural difference in dielectric properties between the BMVs and the surrounding plasma fluid to quickly and consistently collect these particles from as little as 25 µL of plasma. Using DEP and immunofluorescence staining of the LPS biomarker carried on BMVs, we have demonstrated a lower limit of detection of 4.31 × 109 BMVs/mL. The successful isolation of BMVs from human plasma using DEP, and subsequent on-chip immunostaining for biomarkers, enables the development of future assays to identify the presence of specific bacterial species by analyzing BMVs from small amounts of complex body fluid.